The influence of Islam on the statecraft and legal writing in Pre-Colonial Malay society - Sulkafle, Mohamad Hazizie (Penerbit UMT, 2022)
Syed Muhammad Naquib al-Attas, in Islam dalam Sejarah dan Kebudayaan Melayu (1999) convincingly argues that the arrival of Islam in the Malay world has introduced significant changes in society. In so doing, Al-Attas has successfully refuted the long-held views of some Orientalists on the subject. These Orientalists, epitomized by Christian Snouck Hurgronje, Jacob Cornelis van Leur and Thomas Stamford Raffles claim that Islam was just a “thin layer” covering the Malay society. Furthermore, R.O. Winstedt had dismissed that many aspects of Malay culture, literature, and civilisation are borrowed from India. Though during the initial phase, Islam spread gradually but eventually, from the fifteenth century onwards, the influence of Islam in the Malay world had increased tremendously. This was manifested in various spheres of life: culture, laws, politics, language, and society. Two important aspects become the focus of this study namely, the influence of Islam on Malay statecraft and the writing of laws.